2009
DOI: 10.1248/yakushi.129.623
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Tetrandrine, a Natural Inhibitor of <i>Candida albicans</i> Drug Efflux Pumps

Abstract: Synergistic eŠects have previously been observed for a natural compound, tetrandrine (TET), with ‰uconazole (FLC) in vitro and in the treatment of Candida albicans-infected mice. To investigate the mechanisms of these synergistic eŠects, 16 strains of C. albicans from the same parent but with diŠerent FLC sensitivities were examined using ‰ow cytometry and ‰uorescent spectrophotometry. Rhodamine 123 (Rh123)-positive cells and intracellular Rh123 ‰uores-cence intensity were determined in accumulation/eOEux expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Screening for chemosensitization in agar diffusion assays or liquid growth assays has been used to identify inhibitors of fungal efflux pumps. The application of these usually non-high-throughput screens, to panels of xenobiotics (23), combinatorial peptide libraries (33), and libraries of natural products (46) has identified tacrolimus (FK506), milbemycins (23), enniatins, beauvericin, unnarmicins (46), ibuprofen (40), tetandrine (52), cerulenin analogs (9), and some octapeptides (33) as specific fungal ABC pump inhibitors. Ideally, such compounds will inhibit a range of clinically important efflux pumps but not human orthologs.…”
mentioning
confidence: 99%
“…Screening for chemosensitization in agar diffusion assays or liquid growth assays has been used to identify inhibitors of fungal efflux pumps. The application of these usually non-high-throughput screens, to panels of xenobiotics (23), combinatorial peptide libraries (33), and libraries of natural products (46) has identified tacrolimus (FK506), milbemycins (23), enniatins, beauvericin, unnarmicins (46), ibuprofen (40), tetandrine (52), cerulenin analogs (9), and some octapeptides (33) as specific fungal ABC pump inhibitors. Ideally, such compounds will inhibit a range of clinically important efflux pumps but not human orthologs.…”
mentioning
confidence: 99%
“…Many naturally occurring compounds, such as curcumin, berberine, and tetrandrine, show promising antifungal activity (27,41,47,52). However, these compounds are active at high concentrations, in contrast to established antifungal agents, such as azoles, allylamine, and polyenes.…”
mentioning
confidence: 99%
“…Furthermore, analysis of R6G efflux revealed that TET could inhibit the drug efflux pump of A. fumigatus. Zhang et al (2009) also demonstrated that the synergistic mechanism of TET with fluconazole against C. albicans was related to inhibition of the drug efflux pump and downregulation of drug efflux pump genes. Guo et al (2014) found that the synergistic mechanism of TET to fluconazole against C. albicans was related to the generation and transport of ATP, resulting in reduced utilization of ATP and inhibition of drug efflux pump activity.…”
Section: Discussionmentioning
confidence: 92%